2018
DOI: 10.1590/1679-78254599
|View full text |Cite
|
Sign up to set email alerts
|

Finite element study of effective width in steel-concrete composite beams under long-term service loads

Abstract: In this work, a finite element-based approach is presented to study the effective width variation in non-pre-stressed steel-concrete beams under the serviceability stage, including time dependent effects such as concrete creep, shrinkage and cracking. For this purpose, the viscoelasticity theory in conjunction with a nonlinear cracking monitoring algorithm is used to trace the nonlinear viscoelastic response of the structure along time. The present numerical model is fully three-dimensional and permits the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…These elements were pre-dimensioned according to the recommendations of AASHTO (2017). Furthermore, research has shown that the main parameters that influence the effective width are the slab height, span length, load type and application, the distance between beams and webs in the cross section and the steel-concrete interaction degree (Castro et al, 2007;Dezi et al, 2006;Gara et al, 2011;Hu et al, 2009;Reginato et al, 2018;Silva and Dias, 2018;Yuan et al, 2016;Zhu et al, 2015). Therefore, the parametric analysis variables were:…”
Section: Parametric Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…These elements were pre-dimensioned according to the recommendations of AASHTO (2017). Furthermore, research has shown that the main parameters that influence the effective width are the slab height, span length, load type and application, the distance between beams and webs in the cross section and the steel-concrete interaction degree (Castro et al, 2007;Dezi et al, 2006;Gara et al, 2011;Hu et al, 2009;Reginato et al, 2018;Silva and Dias, 2018;Yuan et al, 2016;Zhu et al, 2015). Therefore, the parametric analysis variables were:…”
Section: Parametric Analysismentioning
confidence: 99%
“…For the effective width study, the normal stresses in the slab were analyzed at the beginning of the concrete slab plastic behavior because the effective width cannot be measured when such an element reaches the plastic behavior. In this situation there is a uniform stress distribution and it would not be possible to analyze the shear lag effect (Amadio and Fragiacomo, 2002; Reginato et al, 2018).…”
Section: Numerical Effective Width Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Box girder is an important type of bridge structure. For box girder, many scholars have conducted research on shear lag, effective width [1][2][3][4][5], and live load distribution factors [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Internal unbonded tendons may slip in relation to the surrounded concrete along its entire length, whereas external tendons only slip at deviator devices located along the longitudinal direction of the steel beam. The model is based on the enhacement of a previous model called VIMIS, developed by the authors, and which have served as FE tool for other numerical studies , Dias et al 2015, and Reginato et al 2018. The strategy for including internal and external prestressing and some aspects of the numerical modeling of composite beams are then commented in the following sections.…”
Section: Introductionmentioning
confidence: 99%